2020
DOI: 10.1126/science.aaw5473
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming and cancer progression

Abstract: Metabolic reprogramming is a hallmark of malignancy. As our understanding of the complexity of tumor biology increases, so does our appreciation of the complexity of tumor metabolism. Metabolic heterogeneity among human tumors poses a challenge to developing therapies that exploit metabolic vulnerabilities. Recent work also demonstrates that the metabolic properties and preferences of a tumor change during cancer progression. This produces distinct sets of vulnerabilities between primary tumors and metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
1,120
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,434 publications
(1,128 citation statements)
references
References 123 publications
(136 reference statements)
7
1,120
0
1
Order By: Relevance
“…More and more cancer researchers are focusing their attention on the mechanism of tumor metabolic changes. A recent study pointed out that the heterogeneity of metabolic reprogramming in the tumor is clearly related to the outcome of the tumor [26]. New cancer treatments targeting metabolic pathways are being studied in many tumors.…”
Section: Discussionmentioning
confidence: 99%
“…More and more cancer researchers are focusing their attention on the mechanism of tumor metabolic changes. A recent study pointed out that the heterogeneity of metabolic reprogramming in the tumor is clearly related to the outcome of the tumor [26]. New cancer treatments targeting metabolic pathways are being studied in many tumors.…”
Section: Discussionmentioning
confidence: 99%
“…All the steps of the metastatic cascade, from escape of tumor cells from the primary tumor up to emergence of lethal macrometastases, are mirrored by tumor metabolism and metabolic rewiring. It is also clear that survival in the metastatic environment imposes metabolic requirements distinct from those supporting cell growth; inhibition of these adaptive activities results in decreased metastatic spread [ 145 ]. Moreover, it is becoming increasingly evident that this metabolic plasticity contributes significantly to the primary (and acquired) therapeutic resistance of metastatic cancer [ 146 ].…”
Section: Metabolic Rewiring and Metastasismentioning
confidence: 99%
“…As noted above, the metastatic cascade is a highly inefficient process characterized by the presence of multiple bottlenecks, but metabolic reprogramming enables successful navigation through some of these barriers [ 145 ]. Initial steps of local invasion and intravasation require release of CO2, lactate, and other organic acids from metabolically active tumor cells promoting acidification of tumor microenvironment, decrease in the number of adherens junctions between tumor cells, and degradation of ECM [ 147 ].…”
Section: Metabolic Rewiring and Metastasismentioning
confidence: 99%
“…Cancer cells undergo extensive metabolic reprogramming including the typical aerobic glycolysis or the Warburg effect, which involves the switch of a multitude of metabolic enzymes to support the diversion of metabolites that facilitate glycolytic fermentation for energy metabolism even under ambient oxygen conditions [1][2][3][4] . Compelling literatures have recently revealed that many glycolytic enzymes have moonlighting activities in regulating gene expression [5][6][7] .…”
Section: Taken Together This Study Establishes a Novel Role For Thementioning
confidence: 99%